Users of a citizen science platform for bird data collection differ from other birdwatchers in knowledge and degree of specialization - Christoph Randler (Global Ecology and Conservation, 2021)
Citizen Science (CS) projects are important for scientific research and for biodiversity conservation. In ornithology, citizen scientists make important contributions to biological conservation, because they have a highly developed knowledge about birds, making their data more valuable than those from lay persons. However, to make the data even more valuable for conservation, it is important to learn more about the citizen scientists themselves. In this study, birdwatchers using a CS portal for data collection (ornitho) were compared with birdwatchers not using it. The theoretical framework was based on the recreation specialization concept. Different measurements for birding specialization and demographics were used in an online questionnaire survey. A total of 2964 people participated in the study (1119 (37.8%) were ornitho users; mostly from Germany; 1551 (52.3%) were males). Men more than women were submitting observations to the CS platform. Users of the platform scored significantly higher in skill/competence, behavior, and in commitment than non-users, with medium to large effect sizes. However, CS users were significantly younger than non-users. CS users reported to be able to identify 4 times more bird species by song and appearance and spent more days birdwatching, owned more bird books and a more expensive equipment compared with non-users. Higher specialized birdwatchers contributed more observations to the citizen science platform. The study shows considerable differences between birdwatchers using the CS platform ornitho and non-using birdwatchers. This gives some insight into different specialization grades and supports the view that CS data from such portals have important conservation implications.